Groundwater-dependency and water relations of four Myrtaceae shrub species during a prolonged summer drought - Groom, Philip (2003)
Seasonal water relations and water source (δH analysis) data were examined for four Myrtaceae shrub species inhabiting a winter-wet depression (dampland) and surrounding landscape on Perth’s coastal sandplain. Data were collected during an exceptionally dry spring-autumn periodin 2000/2001. The two species occurring within the dampland, Astartea fascicularis and Pericalymma ellipticum, were probably accessing shallow soil moisture or groundwater (at a depth of 0.35 m) during October 2000 (spring), but were not accessing groundwater (at a depth of 1.45 m) duringthe summer drought (March 2001). Species occurring on the dampland embankment (Hypocalymma angustifolium, Eremaea pauciflora) and at a site further upslope (E. pauciflora only) had a significant reduction in predawn xylem water potential and morning stomatal conductance in response to the summer drought, with neither species accessing groundwater during summer. The dampland species were able to maintain summer morning stomatal conductances similar or greater than the conductance measured during the previous spring, implying that shallow soil moisture (gravimetric content of 10–20%) was sufficient to sustain their summer water-use requirements. δH data suggests that P. ellipticum may have been utilising groundwater in early winter (July 2001), implying that the minimum accessible groundwater depth for this species at the study dampland is approximately 1.4 m.